(untitled) (Docentes 2.0 Journal, 2021)
COVID-19 came to affect the whole world in different areas; the World Health Organization (WHO) on March 11, 2020, declared: the virus outbreak can be characterized as a pandemic, derived from the increase in the number of existing cases, considering a public health emergency of international relevance. The objective of this research was to analyze the didactic strategies of the new role of the teaching-learning process entirely at a distance with educational, technological tools in the face of COVID-19. The methodology used was a quantitative, descriptive cross-sectional approach through a questionnaire in Google form, some responses based on the Likert scale, others closed, with a random sample of 200 students from the Centro Universitario del Norte University of Guadalajara, Mexico. It was found that the actors have an unfavorable opinion in some teachers regarding the knowledge and use of a variety of technological tools within the distance teaching-learning process, respecting their class schedule of the virtual educational program, with social networks being a vital communication factor during confinement. With these findings, new educational policies with the integration of ICTs were proposed, training teachers as students on various educational tools.